2012
DOI: 10.1097/tp.0b013e31824cd5e6
|View full text |Cite
|
Sign up to set email alerts
|

Control of Blood Pressure in Liver Transplant Recipients

Abstract: BP is not adequately controlled in a noticeable percentage of liver transplant patients, especially in subjects with diabetes or metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Another important finding of this study is that all the CV risk factors assessed, except tobacco use, showed a continuous increase during the follow‐up that is evident since the first 6 months after LT. Notably, in accordance with other reports, the control of diabetes, dyslipidemia, and arterial hypertension worsened during the 5 years after LT . Despite the relatively short follow‐up of this series that may not allow us to fully capture the longterm impact of the new‐onset CV risk factors on late CV morbidity, this study revealed that the development of new‐onset CV risk factors may modify the CV risk in the first 5 years after transplantation.…”
Section: Discussionsupporting
confidence: 85%
“…Another important finding of this study is that all the CV risk factors assessed, except tobacco use, showed a continuous increase during the follow‐up that is evident since the first 6 months after LT. Notably, in accordance with other reports, the control of diabetes, dyslipidemia, and arterial hypertension worsened during the 5 years after LT . Despite the relatively short follow‐up of this series that may not allow us to fully capture the longterm impact of the new‐onset CV risk factors on late CV morbidity, this study revealed that the development of new‐onset CV risk factors may modify the CV risk in the first 5 years after transplantation.…”
Section: Discussionsupporting
confidence: 85%
“…57,58 The molecular mechanism has not been fully elucidated, but it appears to involve intracellular oxidative stress, dysregulation of cytokines, inhibition of insulin downstream signaling, and reduced expression of glucose transporters. [59][60][61] Furthermore, it has long been noted that HCV infection may cause mixed cryoglobulinemia and immunemediated glomerulonephritis, 62,63 which can progress to renal failure. Because the presence of atherosclerosis in the peripheral artery may indicate a more diffuse process, this finding suggests that the pathogenic role of HCV is limited during the early phase of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we recently published a multicenter Spanish study on control of blood pressure hypertension in almost 1000 LT recipients and we found that almost one‐third of the patients known to be hypertensive have an inadequate control of their blood pressure. Another remarkable result in our study was that 25% of patients never diagnosed as hypertensive after transplantation had increased blood pressure at the time of the study.…”
Section: Discussionmentioning
confidence: 99%